KARAKTERISTIK BUTIR SOAL TES MATA KULIAH MATRIKS & RUANG VEKTOR MAHASISWA MATEMATIKA - Anggrina Gusmizain (Jurnal Evaluasi Pendidikan, 2022)
The purpose of this research is to obtain information about the characteristics of the items that provide an overview of the evaluation of the test questions and can be used as input in the preparation of further test questions using the anates program description version 4. The method used in this research is case study research with a quantitative descriptive approach. In this study, there were 75 mathematics students at Sebelas Maret University who took courses on matrices and vector spaces. This study focused on the analysis of validity, reliability, discriminatory power, and level of difficulty. The research instruments used were test questions, answer keys, and test results. The test used in the form of subjective questions as many as 10 items. The results showed that the validity of the items was valid and significant, highly reliable with a reliability index of 0.777, the level of difficulty was dominated by the very easy category with a percentage of 70%, and poor discriminatory power with a percentage of 50%.